Development of prototype handicraft utilizing gumamela (Hibiscus Rosa-Sinensis) fibers - Aquino, Athena C.; Malicdem, Eleanor A. (2007.)
This study was conducted to develop a new raw material fiber for handicraft product, the gumamela bast fiber. Specifically, this exploratory study aimed to identify technique in extraction of gumamela bast fibers and to develop prototype handicraft products made from this fiber. Selected attributes of developed gumamela handicraft products were also assessed using abaca product as standard. The study is divided in five phases or stages. Phase I to IV was on the procedure of extracting gumamela bast fibers, fiber analysis, concept design, and handicraft production. The last stage, Phase V, was the conduct of simple survey to compare the physical properties or attributes of gumamela and abaca products. Five thousand grams of gumamela branches were defoliated and retted for thirty days in a pit of water. Extracted retted fibers were found to be lustrous, pliable, and creamy white in color. Laboratory testing and analysis of physical properties showed that gumamela fiber possessed fiber properties such as tensile strength, fineness or densier, has moisture and residual gum content. These were indicators to suggest the possibility of using the gumamela fiber for handicraft construction. Twenty seven (27) prototype products were developed by applying twining, crocheting, braiding, coiling, weaving, glueing, cutting and tying techniques. Eight fiber attributes were identified to be necessary in handicraft construction techniques namely: color, luster, texture, appropriateness of design to function, appropriateness of design to materials, pliability, fiber weight and tensile strength. These attribute were evaluated using the abaca product as standard through a survey. Result of the survey showed that although abaca product was rated higher, gumamela product obtained comparable scores [overall ratings: 3.76 (gumamela) vs. 4.11 (abaca)]. On pliability, both products received the same ratings. Based on the result of the laboratory analysis and the survey, gumamela fiber can be a possible alternative raw material for handicraft products.
Thesis (Ph.D.HE)--University of the Philippines Diliman
Keywords: Handicrafts -- Philippines; Hibiscus -- Philippines